A strategy for bioremediation of nuclear contaminants in the environment. (15th February 2023) - Li, Zhaolin; He, Yifeng; Sonne, Christian; Lam, Su Shiung; Kirkham, Mary Beth; Bolan, Nanthi; Rinklebe, Jörg; Chen, Xiangmeng; Peng, Wanxi
Abstract: Radionuclides released from nuclear contamination harm the environment and human health. Nuclear pollution spread over large areas and the costs associated with decontamination is high. Traditional remediation methods include both chemical and physical, however, these are expensive and unsuitable for large-scale restoration. Bioremediation is the use of plants or microorganisms to remove pollutants from the environment having a lower cost and can be upscaled to eliminate contamination from soil, water and air. It is a cheap, efficient, ecologically, and friendly restoration technology. Here we review the sources of radionuclides, bioremediation methods, mechanisms of plant resistance to radionuclides and the effects on the efficiency of biological adsorption. Uptake of radionuclides by plants can be facilitated by the addition of appropriate chemical accelerators and agronomic management, such as citric acid and intercropping. Future research should accelerate the use of genetic engineering and breeding techniques to screen high-enrichment plants. In addition, field experiments should be carried out to ensure that this technology can be applied to the remediation of nuclear contaminated sites as soon as possible. Graphical abstract: Image 1 Highlights: A comprehensive review on bioremediation of radionuclides and influencing factors. Radionuclides from nuclear contamination bring harm to environment and public. Bioremediation offers a low-cost approach with little environmental impact. In the future, it is necessary to use genetic engineering and breeding methods to breed high-enrichment plants.